(untitled) (Fiep Bulletin - online, 2014)
It is well-estabilished that physical inactivity and low fitness level have been considered risk factors for early mortality which are as important as smoking, dyslipidemias and hypertension. Similarly, the excessive consumption of fat also contributes for the increase of obesity and cardiovascular disease risk. The aim of this study was to describe lipid consumption related to the level of physical activity (PA) of adults in Vale do Sinos, RS. For this study, 597 subjects from 18 to 81 years old were selected according to the residence criterion of Instituto Brasileiro de Geografia e Estatística - IBGE, living in towns in Vale do Sinos, RS. BMI was calculated through height and body mass. The level of PA was assessed through the application of the International Physical Activity Questionnaire (IPAQ), short version. Lipid consumption was calculated through 24h food record. ANOVA, from the statistical package SPSS 12.0, was used in order to test differences between PA levels, considering p<0.05. More than one third of the subjects analyzed consumed lipids above nutritional recommendations (25-30% of Total Energy Intake -TEI). Although the statistical test does not show significant difference between the groups, there was a tendency for a higher number of subjects classified as insufficiently active (IA) to consume lipids above recommended levels when compared to sufficiently active (SA) and highly active (HA) ones. The study identified that 54.5% of the subjects who consumed more than 30% of TEI in lipids and were IA showed overweight or obesity. In conclusion, we did not find statistically significant difference in lipid consumption between PA levels. However, low levels of physical activity seem to be more present among individuals who consume lipids above recommended levels. This leads to a profile of compromised health, which contributed for an increase in coronary artery disease risk.